Pengaruh Perapihan pada Berbagai Stratifikasi Hutan Lepas Tebang terhadap Permudaan - S Sahid (Jurnal Manajemen Hutan Tropika, 2009)
The study of the effects of the clean activities of forest layers in logged areas on the increments of forest value comprises measurement by aerial photograph with scale of 1 : 20.000 and measurement in the field. The stand parameters measured are the percentage of crown cover (C), tree height (H) and crown diameters (D). Whereas, forest values are defined through the measurements of the amounts and qualities of rejuvenations counted after 1 year, 3 year, and 5 year of tidiness. The forest stratums resulted were Cl = 211.6 ha; C2 = 492.0 ha; and C3 = 196.4 ha. The t test conducted in every stratum showed that the tidiness affected significantly on the the amounts and qualities of rejuvenations. It could be concluded that the clean up activities increased the forest values.